The modification, elaboration and empirical evaluation of the De Goede learning potential structural model through the incorporation of non-cognitive learning competency potential latent variables - Du Toit, Berne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MCom)--Stellenbosch University, 2014.